Pemanfaatan Ecobrick untuk Mendukung Perilaku Hidup Bersih dan Sehat di Lingkungan SDN Palasari 03 - Mukhlishah; Afanin; Fadila, Elsa Suci; Hanifah, Ghina Nurul; Khairunnisya, Natasya Rizkya (Bayani, 2024)
Indonesia, being the fourth most populous country in the world with a high consumption rate, has resulted in an increasing amount of waste generated from various sectors. One of them is plastic waste. Plastic, being a widely used material in daily life, has made the problem of plastic waste increasingly severe and a serious challenge for the environment. Ecobricks are one of the solutions that can be developed to reuse plastic waste by transforming it into useful objects. The aim of this program is to introduce and train students on waste management using the ecobrick method as an effort to reduce plastic waste and increase students' awareness of Clean and Healthy Living Behaviours (PHBS) in the school environment. This socialisation method uses lectures and direct practice of making ecobricks. The results obtained show that students can understand the importance of managing plastic waste into useful objects using the ecobrick method. It is hoped that this activity can continue in the future, and SDN Palasari can become a cadre of initiating plastic waste management in elementary schools.